Evaluasi Kebijakan Pelayanan Perizinan Berusaha Berbasis Risiko di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Bandar Lampung Tahun 2025 - Pebriyanti Sitorus; Eko Budi Sulistio; Apandi Apandi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Risk-based business licensing policy implemented through the Online Single Submission Risk-Based Approach system under Government Regulation Number 5 of 2021 continues to face challenges at the regional level. This is indicated by 230 returned license applications, 746 incomplete submissions, and a decline in investment realization in Bandar Lampung City from 105.93% in 2023 to 63.79% in 2024. This study aims to evaluate the implementation of risk-based business licensing services at the DPMPTSP of Bandar Lampung City and to identify its supporting and inhibiting factors.The study employs a descriptive qualitative approach, with data collected through interviews, observation, and documentation, and analyzed using Hanif Nurcholis’public policy evaluation framework, focusing on process, outputs, and outcomes indicators. The findings show that in the process aspect, services have been effective for low- and low-medium-risk businesses; however, issues remain, including unclear requirements, inconsistencies between the OSS-RBA system and additional local requirements for medium-high and high-risk businesses, and the absence of SLA information, leading business actors to monitor processes outside the system. In terms of outputs, the system has cumulatively issued 51,630 NIB from 2021 to 2025, with accurate targeting based on risk classification, while returned applications indicate a selective and accountable system. Regarding outcomes, the policy has generated positive changes for business actors, although its long-term impact on investment growth remains limited. It is concluded that the policy has been implemented fairly well but not optimally, requiring synchronization between central and local requirements, improvement of SLA functionality, and enhanced responsiveness of central government technical support.